Diseño de un plan de negocios para la exportación de carne de vacuno a Rusia (2020)
During the design of the business plan for exporting beef to Russia from Colombia, quantitative requirements were identified through statistical analysis of: production, exports and imports, technical data and experimental statistics, to demonstrate the demand for cattle meat Beef in the market. In this way, the investment, financing and profitability for the success of the export were determined. Under market expectations, the recovery of the sanitary status as a country free of FMD from Colombia, reopens the international market, leaving behind the loss of more than US $ 120 million, due to the closure of the international market. However, Colombia is the third largest meat producer in Latin America, a consequence of the breeding and fattening of breeds for the production of high-quality meat. The business plan is intended to boost the production and conversion of beef from cattle, since its economy, determined its investment and its financing and achieve profitability.